Tracing Chintāmani Lokeśvara of Itubāhā: A Case Study on the Repatriation of Stolen Art - Shakya, Saraswati Rashmi (Journal of Buddhist Studies (T.U.), 2025)
Nepal experienced numerous statues and paintings of gods and goddesses as well as art and artifacts from the communities were stolen, some got registered while several went unregistered. Itubāhā, which is one of such cultural heritage in Nepala Maṇdala too faced several thefts of its tangible heritages. This case explores the theft of one of the three Paubhās offered to the bāhā. The theft was silent and effective. This case study shows the tracing of the Paubhā and the correspondence made during the pre-internet era and it presents how these communications added to the case. It also showcases the importance of any art/artifact in its place of origin and the legalities that support it. International legal provisions and guidelines that do protect the right of the owner/ source of origin. This provision is one of the major aspects for the repatriations of the stolen art heritage. The value and importance of repatriation for the community is not a matter of prestige but a right; and this fight for rightful ownership continues to date.